1984
DOI: 10.1159/000118127
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Schizophrenia and Psychosomatic Illness: A Review

Abstract: For centuries, a relationship between physical illness and mental illness has been assumed. Following this lead, many reports of an inverse relationship between a number of physical disorders and schizophrenia have appeared. Particularly, the low rates of occurrence of certain psychosomatic illnesses in schizophrenic patients seem to indicate a certain biological and psychodynamic basis. These associations are important in that they may unravel important etiological relationships. Furthermore, they are amenabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1988
1988
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Incidence of psychosomatic disorders had been reported to be low in psychotic patients and high in neurotic patients (Allebeck, Rodvall & Wistedet, 1985;Ananth & Engelsmann, 1984;Nemiah, 1975). Our results further support these previous findings in a quite large sample of patients.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Incidence of psychosomatic disorders had been reported to be low in psychotic patients and high in neurotic patients (Allebeck, Rodvall & Wistedet, 1985;Ananth & Engelsmann, 1984;Nemiah, 1975). Our results further support these previous findings in a quite large sample of patients.…”
Section: Discussionsupporting
confidence: 92%
“…1982;Schwartz, 1951). Bronchial asthma and other allergic disorders are also infrequent (Ananth & Engelsmann, 1984;Baldwin, 1979;Dutta-Ray, 1962;Lipper & Werman, 1977). Allebeck et al (1985) reported a reduced incidence of rheumatoid arthritis among persons with schizophrenia and affective psychoses, but not among patients with neurosis.…”
Section: Discussionmentioning
confidence: 99%